Expert System for Diagnosis Papaya Plant Disease with Backward Chaining and Dempster Shafer - Veronika; Suci Ramadhani; Ida Maratul Khamidah (TEPIAN, 2022)
Papaya plant (Carica papaya L.) it is one of leading commodities in East Kalimantan. Papaya is widely cultivated in Samarinda, Balikpapan, and Samboja. However, farmers are often faced with the problem of papaya plant diseases that can damage and inhibit the growth of papaya plants and fruit. To solve this problem, an expert system was created to diagnose diseases in papaya plants. This expert system was created using two methods, namely Backward Chaining Reasoning and to determine the level of certainty in the diagnosis of papaya plant diseases, the Dempster Shafer method was used. The excepted result of making this expert system is to build an expert system application that can diagnose web-based diseases in papaya plants so that it can make it easier for farmers to consult and get the right solution to overcome various disease problems that attack papaya plants.